Visible Light Effects on Photostrictive/Magnetostrictive PMN‐PT/Ni Heterostructure - Deepak Dagur; Vincent Polewczyk; Aleksandr Yu. Petrov; Pietro Carrara; Marta Brioschi; Sara Fiori; Riccardo Cucini; Giorgio Rossi; Giancarlo Panaccione; Piero Torelli; Giovanni Vinai (Advanced Materials Interfaces, 2022)
Abstract The possibility of modifying the ferromagnetic response of a multiferroic heterostructure via fully optical means exploiting the photovoltaic/photostrictive properties of the ferroelectric component is an effective method for tuning the interfacial properties. In this study, the effects of 405 nm visible‐light illumination on the ferroelectric and ferromagnetic responses of (001) Pb(Mg1/3Nb2/3)O3‐0.4PbTiO3 (PMN‐PT)/Ni heterostructures are presented. By combining electrical, structural, magnetic, and spectroscopic measurements, how light illumination above the ferroelectric bandgap energy induces a photovoltaic current and the photostrictive effect reduces the coercive field of the interfacial magnetostrictive Ni layer are shown. Firstly, a light‐induced variation in the Ni orbital moment as a result of sum‐rule analysis of x‐ray magnetic circular dichroic measurements is reported. The reduction of orbital moment reveals a photogenerated strain field. The observed effect is strongly reduced when polarizing out‐of‐plane the PMN‐PT substrate, showing a highly anisotropic photostrictive contribution from the in‐plane ferroelectric domains. These results shed light on the delicate energy balance that leads to sizeable light‐induced effects in multiferroic heterostructures, while confirming the need of spectroscopy for identifying the physical origin of interface behavior.